2021
DOI: 10.3389/feart.2021.676775
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Earthquake Precursors From Space: A Critical Review

Abstract: Starting from late seventies, many observations have been reported about observations in space of signals reconciled with earthquakes and claimed as possible preseismic measurements. The detected parameters range from electromagnetic field components (in a large band of frequencies) to plasmas parameters; from particles detection to thermal anomalies; etc. Up to the DEMETER mission, the analyses have been carried out on datasets gathered by not devoted satellites. Even beyond the results obtained, the DEMETER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 220 publications
0
28
0
Order By: Relevance
“…As mentioned above, beyond the mechanical oscillations (of the ground surface or of the atmospheric layers), the geochemical fluids variations and the thermal anomalies, the list of proposed earthquake-precursors on ground includes many observations of electromagnetic disturbances. We will concentrate only on measurements on ground, addressing to the companion article by Picozza et al (2021) on the same volume for a review of the space born detection of possible seismo-electromagnetic precursors.…”
Section: Seismo-electromagnetic Perturbations Detected On Groundmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, beyond the mechanical oscillations (of the ground surface or of the atmospheric layers), the geochemical fluids variations and the thermal anomalies, the list of proposed earthquake-precursors on ground includes many observations of electromagnetic disturbances. We will concentrate only on measurements on ground, addressing to the companion article by Picozza et al (2021) on the same volume for a review of the space born detection of possible seismo-electromagnetic precursors.…”
Section: Seismo-electromagnetic Perturbations Detected On Groundmentioning
confidence: 99%
“…for a joint analysis of such complex and interrelated system (Ouzounov et al, 2018). Because data needed for these investigations are collected both on ground and by satellite, we address the reader to the companion article Picozza et al (2021) and to therein references, where this topic is further discussed for space-based observations of precursors. The possible correlation between seismic events and fluctuation of water column content has been studied for example by Dey et al (2004) for the 2001 M7.8 Gujarat earthquake; by Ma et al (2010) for the Hengchun (Taiwan) M 7.2 event of 2006 and by Wu et al (2016) for the 2009 M6.2 L'Aquila earthquake.…”
Section: Multi-parametric Analyses Looking For Earthquake Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we will deal with the delicate research on the possible precursors of earthquakes, i.e., those anomalous phenomena that might appear before earthquakes because they are caused by their preparation phase and thus anticipate their imminent occurrence. The earthquake precursors could be simply classified as seismic precursors and non-seismic precursors: the former are eventual modifications of seismicity or seismological parameters before the occurrence of an earthquake, while the latter, the object of our present research, are alterations of some geophysical parameters, such as atmospheric chemical and physical characteristics, radon emission, and, furthermore, possible electromagnetic disturbances up to the ionosphere [1][2][3]. Historically, some evidence of electromagnetic precursors has been reported in the data from ground magnetic observatories-for example, before the M6.9 Spitak (Armenia) 1988 and M7.1 Loma-Prieta 1989 earthquakes by Fraser-Smith et al [4] and Molchanov et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we summarize what is happening in the upper ionosphere, such as the F region of the ionosphere [82,83]. Our extensive analyses both on the TEC and ionosonde observational data have indicated that no clear anomalies are detected during the last phase of EQ preparation, unlike the situation in the lower ionosphere.…”
mentioning
confidence: 96%